Pengembangan Modul Pembelajaran Materi Wujud Zat dan Perubahannya Berbasis Etnosains "Tape Bondowoso" Terhadap Kemampuan Literasi Sains Siswa - Intan Triwulandari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Science literacy is one of the essential competencies required in 21st-century education. However, the level of students’ science literacy in Indonesia is still relatively low, as indicated by the 2022 Programme for International Student Assessment (PISA) results. One approach that can support the improvement of science literacy is ethnoscience-based learning, which integrates local cultural knowledge into science education. This study aims to develop an ethnoscience-based learning module on the topic of states of matter and their changes using the local context of “Tape Bondowoso” and to determine its validity, practicality, and effectiveness in improving students’ science literacy. This research employed a Research and Development (R&D) method using the Borg and Gall development model, implemented up to the eighth stage. The study was conducted at SDN Wonosari 02 Bondowoso with 20 fourth-grade students as research subjects. Data were collected through validation sheets, student response questionnaires, and science literacy tests. The data were analyzed using descriptive statistical analysis.The results showed that the developed module was categorized as very valid, with an average validation score of 90% from material, language, and media experts. The practicality test indicated a score of 91%, categorized as very practical. Furthermore, the effectiveness test showed an average N-Gain score of 0.62, which falls into the moderate category, indicating that the module effectively improved students’ science literacy. Therefore, the ethnoscience-based learning module using the context of Tape Bondowoso is valid, feasible and effective as a learning resource to support science literacy in elementary school students.
Approved by Teddy
Keywords: ethnoscience; learning module; science literacy; states of matter; Tape Bondowoso